Perceptions of Healthcare Access Barriers Among Eritrean, Sudanese, and Somali Refugees and Asylum Seekers in Cairo. - Mohamed, Ayan Musa (AUC Knowledge Fountain, 2026)
As the world witnesses an increase in different displacements of individuals for various reasons, ranging from wars, civil conflicts, human rights violations, and natural disasters, refugees and asylum seekers, who are among those forcibly displaced, continue to face challenges in access to health care services in host countries. The topic of barriers to health care has been widely researched, with a large body of literature on refugees' interactions with health care systems. However, there is limited literature on the perceptions of Eritrean, Sudanese, and Somali refugees and asylum seekers' experience with healthcare access in host countries. Therefore, this thesis aims to address this gap by focusing on the perceived barriers to health care access in Cairo, Egypt, among Eritrean, Sudanese, and Somali refugees and asylum seekers. This study utilized a mixed-methods approach; quantitative data were collected by distributing the Perceived Access to Healthcare Questionnaire (PAHQ) to a sample of 233 individuals. Focus group discussions were conducted with 30 individuals from the three communities to gather the qualitative data. Quantitative data were analyzed using R software, and deductive, inductive thematic analysis was employed to analyze the qualitative data. Results showed that participants faced barriers in approachability, acceptability, affordability, availability, and accommodation dimensions of healthcare access. Results also showed that gender, age, and nationality were significant predictors of perceived barriers, while refugee status was not a significant predictor.